Shakespeare à l’écran : Makibefo d’Alexander Abela, un exemple extrême d’appropriation culturelle - Anne-Marie Costantini-Cornède (Revue LISA)
Alexander Abela’s Makibefo (1999) shot in Madagascar and played by non-professional actors. The use of the Antandroy people or “an ancient tribe” who had never even seen a film before, is an example of cultural appropriation or a “transcultural” approach to the play, a complex process of rewriting which consists in a narrative and aesthetic remoulding of the play adapted. By transposing the play Macbeth to an unusual context, a poor fishermen’s village lost at the other end of the world, the filmmaker means to enhance its mythic and universal dimension. He resorts to various narrative and aesthetic strategies such as plot displacements, character suppressions or dialogue simplifications as well as ample and systematic use of cinematic rhetoric (camera movements, framing and angle shot effects or light contrasts), which helps create a filmic mode. The process is paradoxical, as it is not so much meant to deconstruct the play as to reconstruct its essential meaning in a novel, powerful and visionary way, thus offering an alternative reading of the play.